لحفظ المفردات العربية لبرنامج تطوير اللغة الأجنبية في معهد غاله سينجونانجونج بورواساري باسوروان KAISA تأثير طريقة - Syarifuddin; Nafisatul Ainiyah (Universitas Yudharta Pasuruan, 2021)
This study aims to determine whether there is a significant influence on the implementation of the Kaisa method to memorize Arabic vocabulary between the experimental group (using the Kaisa method) and the control group (not using the Kaisa method). This research is a quantitative research. The sample in this study consisted of 32 students, consisting of 16 students who were in the experimental class and 16 students who were in the control class. The data collection techniques using observation, interviews and tests. The analysis used is comparative analysis using the